2005
DOI: 10.1007/bf02724013
|View full text |Cite
|
Sign up to set email alerts
|

Leukodystrophies: Indian scenario

Abstract: The leukodystrophies are familial disorders with onset usually in infancy or childhood. The clinical features consist of motor dysfunction with varying degree of cognitive decline. Magnetic Resonance Imaging (MRI) has helped to identify and characterize these disorders. In some leukodystrophies, biochemical enzymatic and genetic defects have been identified. The commonest leukodystrophy seen in India is Megalencephalic Leukodystrophy with subcortical cysts. The essential features consist of large head, mild py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…This may be associated with low physical activity and high dietary calorie and fat intake . Among neurologic diseases, limb‐girdle muscular dystrophy and megalencephalic leukodystrophy with subcortical cysts are relatively more prevalent among the same ethnic group …”
Section: Discussionmentioning
confidence: 99%
“…This may be associated with low physical activity and high dietary calorie and fat intake . Among neurologic diseases, limb‐girdle muscular dystrophy and megalencephalic leukodystrophy with subcortical cysts are relatively more prevalent among the same ethnic group …”
Section: Discussionmentioning
confidence: 99%
“…The gene pool is expected to be heterogeneous but with pockets of homogeneity because of the general trend of marriages within closed communities. The Agarwal community is a large enterprising community consisting of affluent business-class North Indian population originating from a small town of Agroha, near Delhi and spreading all over the world (Singhal 2005). Genetic studies have suggested founder effect in Agarwals in some other genetic disorders like megalencephalic leukoencephalopathy with subcortical cysts (MLC, OMIM #604004), spinocerebellar ataxia type 12 (OMIM #183090), and pantothenate kinase-associated neurodegeneration (PKAN, OMIM#234200) (Gorospe et al 2004;Bahl et al 2005;Chabbria et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Singhal BS in his paper states that commonest leukodystrophy seen in India is Megalencephalic Leukodystrophy with sub-cortical cysts[7]; seen more in the Agarwal community in India.…”
Section: Discussionmentioning
confidence: 99%